View of the fallen Mandapa of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
View of the fallen mandapa (pillared hall) and the entrance to the garbhagriha (sanctum sanctorum) of the Chaunsath Yogini Temple. The layout of the mandapa can be discerned based on the hewn foundation stones of the exterior walls and the pillar positions. It must have been a semi-open type of mandapa, with openings on the west, south, and north sides. The remnant portions of the interior walls of the mandapa indicate that these must have been plain in comparison to its interior.